Analisis Lengkung Intensitas Hujan Dengan Beberapa Pendekatan di Kota Bekasi - Segel Ginting (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2022)
The empirical methods of intensity duration frequency are most often used with limited data. Its information is needed to design a drainage system. This study aims to obtain the best empirical method that can describe the curve of intensity duration frequency in Bekasi. These methods use the Mononobe, van Breen, and Bell methods and are then calibrated with intensity duration frequency curves derived from short-duration data (observation). The result shows that no empirical techniques best fit the words. However, the Mononobe method has fewer results than the Bell, van Breen, and observations. When the three practical methods were compared with the comments, the Bell method was the most suitable approach for determining the rain intensity for a return period of under five years. In contrast, the van Breen method was for a return period of more than five years.